KEBUTUHAN PERAWATAN ORTODONTI BERDASARKAN INDEX OF ORTHODONTIC TREATMENT NEED PADA REMAJA - Hikmah Nurfajri Suala; Diana Wibowo; Raden Harry Dharmawan Setyawardhana (Universitas Lambung Mangkurat, 2021)
ABSTRACTBackground: The condition of oral health in Indonesia and the world remains a serious problem. One of the dental and oral health problems with a high prevalence is malocclusion. Malocclusion can be experienced by children, adolescents, and adults. Malocclusion require proper treatment by performing orthodontic treatment. Orthodontic treatment needs can be measured by using a malocclusion index, one of them is the Index of Orthodontic Treatment Need (IOTN). Purpose: The purpose was to determine the need of orthodontic treatment based on the Index of Orthodontic Treatment Need in adolescents. Methods: The literature review with the narrative review analysis method by looked for similarities and dissimilarities, provided viewpoint, compared, and created summaries. Results: The need of orthodontic treatment based on the Index of Orthodontic Treatment Need showed an average of 60.5% of adolescents did not need orthodontic treatment with the lowest prevalence of 22.4% and the highest prevalence of 96.6%, at the same time, adolescents who urgently needed orthodontic treatment an average of 20.6%, with the lowest prevalence approximately 0.028% and the highest prevalence of 63.3%. Conclusion: The level of orthodontic treatment needs based on the Index of Orthodontic Treatment Need showed that an average of 60.5% of adolescents did not need orthodontic treatment and an average of 20.6% of adolescents were in highly need of orthodontic treatment. Through this study, the community was expected to take care of dental and oral health, especially related to malocclusion to prevent the increase of orthodontic treatment needs. Keywords: adolescents, index, orthodontic treatment need, school children ABSTRAKLatar belakang: Kondisi kesehatan gigi dan mulut masyarakat di Indonesia maupun dunia masih menjadi masalah serius. Salah satu masalah kesehatan gigi dan mulut dengan prevalensi tinggi adalah maloklusi. Maloklusi dapat dialami oleh anak-anak, remaja, hingga orang dewasa. Kondisi maloklusi membutuhkan penanganan yang tepat yaitu dengan melakukan perawatan ortodontik. Kebutuhan perawatan ortodonti seseorang dapat diukur menggunakan indeks maloklusi, salah satunya dengan Index of Orthodontic Treatment Need (IOTN). Tujuan: Tujuan studi literatur ini adalah untuk mengetahui kebutuhan perawatan ortodonti berdasarkan Index of Orthodontic Treatment Need pada remaja. Metode: Literature review dengan metode analisis narrative review dengan mencari kesamaan, mencari ketidaksamaan, memberikan pandangan, membandingkan, dan membuat ringkasan. Hasil: Kebutuhan perawatan ortodonti berdasarkan Index of Orthodontic Treatment Need menunjukkan rata-rata 60,5% remaja tidak membutuhkan perawatan ortodonti dengan prevalensi paling rendah sebesar 22,4% dan prevalensi paling tinggi adalah 96,6%, sedangkan remaja yang sangat membutuhkan perawatan ortodonti rata-rata 20,6% dengan prevalensi paling rendah sekitar 0,028% dan prevalensi paling tinggi adalah 63,3%. Kesimpulan: Tingkat kebutuhan perawatan ortodonti berdasarkan Index of Orthodontic Treatment Need menunjukkan bahwa rata-rata 60,5% remaja tidak membutuhkan perawatan ortodonti dan rata-rata 20,6% remaja sangat membutuhkan perawatan ortodonti. Melalui studi ini masyarakat diharapkan dapat menjaga kesehatan gigi dan mulutnya khususnya terkait maloklusi untuk mencegah peningkatan kebutuhan perawatan ortodonti. Kata kunci: anak sekolah, indeks, kebutuhan perawatan ortodonti, remaja